New Predictors of Future Expectations in Peruvian University Students: A Study Conducted in Post-Pandemic Times - Daniel David Calizaya-Rios; Evelyn Doris Mamani Quispe; Lizbeth Lidia Ylachoque Aquima; Liset Z. Sairitupa-Sanchez; Oscar Mamani-Benito (Psiquemag)
The health crisis had negative repercussions on the university experience. Therefore, the aim was to determine if satisfaction with studies, academic self-efficacy, and emotional intelligence predict future expectations in Peruvian university students. Predictive study involving 1650 university students of both sexes, aged between 18 and 42, selected through intentional non-probabilistic sampling. Participants were recruited from private and state universities in the three regions of Peru (Coast, Highlands, and Jungle). Among the faculties they belong to are business sciences, health, engineering, social sciences, humanities, and others. Data were collected through four scales with adequate psychometric properties, and data analysis involved modeling through structural equations. The model showed a good fit to the data: χ2 = 471.743, p < .001, df = 183, CFI = .994, TLI = .993, RMSEA = .056, SRMR = .020. These results support hypotheses H1, H2, and H3, indicating that satisfaction with studies has a positive effect on future expectations (β = .30, p < .001), as does emotional intelligence (β = .27, p < .001) and academic self-efficacy (β = .29, p < .001). Satisfaction with studies, academic self-efficacy, and emotional intelligence predict the future expectations of Peruvian university students. These results have implications for the administrative body responsible for the well-being of the university population in Peru.